Optimalisasi Peran Bidan dalam Pelayanan Kesehatan Lansia Berbasis Pengabdian Masyarakat [Optimizing the Role of Midwives in Community Service–Based Elderly Health Care] - Rahmawati, Vivin Eka; Azizah, Ninik; Fatimah, Nurul; Lubis, Angela Ditauli (UKInstitute, 2026)
The increasing number of older adults in Indonesia has led to a higher risk of health problems, particularly non-communicable diseases. Older adults require promotive and preventive efforts to maintain quality of life and prevent disease complications. This community service activity aimed to improve older adults’ knowledge and to conduct early detection of health problems through health education and health screening. The activity was carried out as part of the FIK Mengabdi program organized by the Faculty of Health Sciences, Universitas Pesantren Tinggi Darul Ulum (Unipdu), on November 20, 2025, in Ngumpul Village, Jogoroto District, Jombang Regency. The participants consisted of 38 older adults, supported by four midwives, two health cadres, one nurses, and one physician. The methods included interactive health education and health screening, such as blood pressure measurement, nutritional status assessment, and brief interviews regarding health complaints. The results showed an improvement in older adults’ understanding of the importance of maintaining health and undergoing regular health check-ups. In addition, the health screening identified several older adults with elevated blood pressure A total of 78% (22 individuals) were identified with hypertension, while 23% (9 individuals) had diabetes mellitus and specific health complaints, allowing for counseling and follow-up recommendations. In conclusion, this activity was effective in increasing health awareness among older adults and supporting promotive and preventive health efforts at the community level. Abstrak. Peningkatan jumlah penduduk lanjut usia (lansia) di Indonesia berimplikasi pada meningkatnya risiko masalah kesehatan, terutama penyakit tidak menular. Lansia memerlukan upaya promotif dan preventif untuk menjaga kualitas hidup dan mencegah komplikasi penyakit. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan lansia serta melakukan deteksi dini masalah kesehatan melalui penyuluhan dan skrining kesehatan. Kegiatan dilaksanakan dalam program FIK Mengabdi yang diselenggarakan Fakultas Ilmu Kesehatan Universitas Pesantren Tinggi Darul Ulum (Unipdu) pada tanggal 20 Nopember 2025 di Desa Ngumpul, Kecamatan Jogoroto, Kabupaten Jombang. Sasaran kegiatan adalah 38 orang lansia, dengan dukungan 4 bidan, 2 kader kesehatan, 1 perawat, dan 1 dokter. Metode yang digunakan meliputi penyuluhan kesehatan secara interaktif dan skrining kesehatan berupa pengukuran tekanan darah, penilaian status gizi, serta wawancara singkat terkait keluhan kesehatan. Hasil kegiatan menunjukkan adanya peningkatan pemahaman lansia terhadap pentingnya menjaga kesehatan dan pemeriksaan rutin. Selain itu, skrining kesehatan berhasil mengidentifikasi beberapa lansia dengan tekanan darah di atas normal yaitu 78% (22 orang), dengan diabetes mellitus 23% (9 orang) dan keluhan kesehatan tertentu, sehingga dapat diberikan konseling dan rekomendasi tindak lanjut. Kegiatan ini disimpulkan efektif dalam meningkatkan kesadaran kesehatan lansia serta mendukung upaya promotif dan preventif di tingkat masyarakat.